Micro, Small, and Medium Enterprises Promoting Sustainable Livelihoods within the South African Context - Ragolane, Mahlatse (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2024)
The objective of this study is to investigate the effects of Micro, Small and Medium Enterprises (MSMEs) in improving sustainable livelihoods. MSMEs are economic growth drivers, particularly in rural and peri-urban regions, through the impetus of social entrepreneurship. South Africa faces several socioeconomic difficulties, which affect most of its population, including unemployment, crime, poverty, and inequality. The formation of small businesses in rural and peri-urban regions has been suggested as a remedy for this condition, to guarantee that people can retain their livelihoods, whether in terms of income or food security. The majority of MSMEs fail to realize their full potential due to problems such as a lack of finance, resources, and knowledge dissemination. The methodology adopted in this paper is qualitative and data was collected using secondary sources and materials. According to the findings of the study, MSMEs have made significant contributions to job creation, poverty alleviation, and GDP growth. It is demonstrated that MSMEs have the potential to ensure that people at the grassroots level do not rely solely on government or incentives. Instead, it can create sustainable lives while contributing to the larger economy, and expanding opportunities for future generations. It is recommended that raising awareness about financial initiatives, business development, and MSMEs support structures is crucial for both the government and private institutions. Moreover, creating more job opportunities requires the public sector to formulate policies and legislation, which support businesses and enable them to compete in the global market.Keywords: MSME, Sustainable Livelihoods, Social Entrepreneurship, Rural and Peri-urban Entrepreneurship, Job Creation.